Desenvolvimento e avaliação da atividade quimiopreventiva de nanopartículas contendo imiquimode em modelo murino de câncer de pele - Dias, Marina França (2018)
Skin cancer has the highest incidence among all types of neoplasms and the tendency is the increasing number of new cases in next decades, wich makes necessary new modalities and treatment options. Chemotherapeutic agent imiquimod is used in treatment of disease, but the high occurrence of local and systemic adverse effects associated with its use as well as its low skin permeation impair adherence and therapeutical effectiveness, respectively. The aim of the present work was evaluate the antitumor activity of nanocapsules imiquimod-loaded compared to its commercial product in murine model of skin cancer. Polymeric nanocapsules containing imiquimod, in the absence and presence of chitosan coating, were obtained by the precipitation of preformed polymer technique and characterized by encapsulation efficiency, size, zeta potential, pH, morphology (transmission electron microscopy and scanning), optical scanning spectrophotometry and in vitro release through dialysis membrane in pH 5.6 buffer. Presence of chemical interactions between formulation components was evaluated by thermogravimetric analysis and infrared spectroscopy. Detection of crystalline structures was performed by X-ray diffractometry. The nanocapsules and commercial imiquimod formulation antiagiogenic activity was determined in a chicken embryo chorioallantoic membrane model. Cutaneous permeation of nanocapsules imiquimod-loaded and commercial imiquimod was determined in Swiss albino mice. The chemopreventive activity of colloidal dispersions and the commercial imiquimod was evaluated through the tumoral inhibition promoted by these treatments in a multi- stage model of chemical carcinogenesis in Swiss mice. Encapsulation efficiency, mean diameter, zeta potential and pH of uncoated nanocapsules imiquimod-loaded were 92.5% ± 0.4; 249 ± 22.4 nm; -40.1 mV ± 3.7 and 5.4 ± 0.01 respectively, whereas for nanocapsules with cationic coating the parameters found were: 88.6 ± 2.3%; 287.0 ± 12.6 nm; + 11.3 ± 0.5 mV and 3.7 ± 0.0, respectively. The formulations morphology obtained by scanning and transmission electron microscopy images confirmed the presence of nanocapsules. In the stability analysis by optical scanning spectrophotometry (Turbiscan), all dispersions obtained a backscattering variation less than 2% over 5 weeks and were considered stable. In the in vitro release assay, imiquimod-loaded nanoparticles obtained slower release of the drug compared to free and commercial imiquimod. There were chemical interactions between chitosan and other formulation components evaluated by thermogravimetric and infrared studies. No crystalline structure was detected by the X-ray diffraction technique for the coated and uncoated imiquimod formulation. The dispersion of nanocapsules containing imiquimod presented antiangiogenic activity superior than commercial formulation in chicken embryo chorioallantoic membrane model. Nanocapsules containing imiquimod both uncoated and coated with chitosan presented cutaneous permeation in deep layers of the skin and inhibition in the chemically induced carcinogenicity process superior than tumor control group and groups treated with placebo nanoparticles while the commercial formulation presented retention of the drug in superficial layers of the skin and did not obtain a statistically significant reduction in the number of papillomas formed compared to the carcinogenic control. These results allow to conclude, therefore, that stable nanocarreadores were obtained and the chemopreventive activity and the antiangiogenic effect of these systems represent a promising alternative for the treatment of cutaneous neoplasias.